Discrepancies in Website Accounting: Non-compliance with ISAK 14: Terungkapnya Ketidaksesuaian: Ketidakpatuhan Pengakuan dan Perlakuan Akuntansi Website dengan ISAK 14 - Mohammad Taufan Prassetiyo; Hadiah Fitriyah (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents a qualitative research study aimed at examining the recognition and accounting treatment of websites as intangible assets. Focusing on the case of the Ricosta website, the research demonstrates that the current practice of categorizing the website as other expenses in financial statements contradicts the guidelines outlined in ISAK 14. By utilizing narrative data and descriptive analysis, the study unveils the misalignment between the recognized accounting treatment and the stipulated requirements. The results highlight the need for adherence to proper recognition and accounting practices for websites as intangible assets, offering implications for companies and standard-setting bodies in promoting accurate financial reporting. Highlights: Non-compliance with ISAK 14: The research uncovers the misalignment between the recognition and accounting treatment of websites as intangible assets and the guidelines stated in ISAK 14. Financial statement impact: The study reveals that the current practice categorizes website expenses as other expenses, contrasting with the potential recognition of websites as intangible assets, which can significantly affect the financial statements of companies. Implications for accurate financial reporting: The findings emphasize the importance of adhering to proper recognition and accounting practices for websites as intangible assets, suggesting implications for companies and standard-setting bodies to ensure accurate and transparent financial reporting. Keywords: website recognition, accounting treatment, intangible assets, ISAK 14, financial statements.